2011
DOI: 10.1039/c1cc11122a
|View full text |Cite
|
Sign up to set email alerts
|

Strongly green-photoluminescent graphene quantum dots for bioimaging applications

Abstract: Strongly fluorescent graphene quantum dots (GQDs) have been prepared by one-step solvothermal method with PL quantum yield as high as 11.4%. The GQDs have high stability and can be dissolved in most polar solvents. Because of fine biocompatibility and low toxicity, GQDs are demonstrated to be excellent bioimaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
1,032
5
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,489 publications
(1,078 citation statements)
references
References 49 publications
36
1,032
5
5
Order By: Relevance
“…A photon-screening effect is also seen in the contour maps showing that the emission wavelength of b-GQDs is excitation independent. At the same pH environment, no apparent PL emission peak shift is observed when b-GQDs are excited from 300 to 400 nm, which is different from other reported GQDs 17,26,32 . This is thought to be due to the more uniform size of the synthesized b-GQDs.…”
Section: Discussioncontrasting
confidence: 51%
“…A photon-screening effect is also seen in the contour maps showing that the emission wavelength of b-GQDs is excitation independent. At the same pH environment, no apparent PL emission peak shift is observed when b-GQDs are excited from 300 to 400 nm, which is different from other reported GQDs 17,26,32 . This is thought to be due to the more uniform size of the synthesized b-GQDs.…”
Section: Discussioncontrasting
confidence: 51%
“…When GQDs were excited at wavelengths from 400 to 540 nm, their PL peak shifted from 515 to 570 nm. [20] Considering the CQ/DMAEMA co-initiator was reported to be excited at the wavelength of 400-500 nm, [21] the PL light from GO enhanced the intensity of the curing light in the experimental adhesive when it was exposed under the LED light curing unit. Thus more free radicals were generated in the GO@SiO2 filled adhesive, which resulted in higher polymerization rate and degree of conversion.…”
Section: Interestingly a Little Increased Ratio Of I(d)/i(g)mentioning
confidence: 99%
“…Additionally, it has been demonstrated that the isolated polyaromatic structures and passivated surface defects also contribute to the fluorescence of GQDs [26,31] Fig. 6 [26]. They also showed that after incubation with cells, fluorescence of GQDs could be observed in dark field, as shown in Fig.…”
Section: Applications For Cell Imagingmentioning
confidence: 60%
“…The intrinsic photoluminescence of GQDs is caused by quantum confinement and edge effect [26,29,30]. Additionally, it has been demonstrated that the isolated polyaromatic structures and passivated surface defects also contribute to the fluorescence of GQDs [26,31] Fig. 6 [26].…”
Section: Applications For Cell Imagingmentioning
confidence: 99%
See 1 more Smart Citation